Analysis of the Effect of Customer Service Competencies in Improving International Freight Forwarding Performance - Purwoko, Harry; Abdurachman, Edi; Saribanon, Euis (Universitas Padjadjaran, 2025)
The performance of Indonesia Logistics is at the lowest rank as per 2023 the Logistics Performance Index of the World Bank. This is due to the freight forwarder’s performance that does the export-import logistics. This research aims to analyze the impact of customer service competencies on improving the freight forwarder’s performance. This quantitative research with five constructs and 23 indicators is validated and proven reliable. The questionnaire was targeted at 210 customer service managers or supervisors in Jakarta to obtain strategic insights into customer service roles in achieving company performance. This research’s result is to build and implement four clear customer service competencies to achieve the freight forwarder’s performance. The customer service competencies have not been previously researched, making this research novel. The results indicate that the competencies of understanding customers, freight forwarding management, customer service management, and stakeholder management positively and significantly affect the freight forwarder’s performance. Strengthening these competencies can enhance operational performance, service quality, delivery effectiveness, and good working relationships with other departments. Implementing customer service competencies will improve freight forwarders’ performance and Indonesia’s logistic rank. Freight forwarders have to pay more attention to developing customer service through specialized training and certification in the freight forwarding industry.